Designing a Lecturer’s Performance Data Warehouse Model Using Star Scheme - Adam Japal; Sutedi Sutedi (Proceeding International Conference on Information Technology and Business, 2021)
Lecturer performance at Sumatera Institute of Technology is very influential in learning activities. In this situation, a comprehensive control is needed. Further, data of lecturers, research, and so on were massive stored in database due to the number of this institution’ lecturers was more than 500 lecturers. Thus, the leader needed a monitoring system to control lecturers’ performance in the institution. To solve thisproblem, it must be something that able to produce information which support monitoring needs. Data warehouse is collection databases were stored in adatabase. It can support the process of making decision based on information was formed from data warehouse. Thus, in this research, warehouse data which contain support information based on tri dharma of university will be formed. Moreover,warehouse data in this research will be formed on 3 schemes. These schemes are Educational Scheme, Research Scheme and Service Scheme will be functionated as data to make leader’s monitoring dashboard. Star Scheme design was chosen to make these 3 schemes. Those schemes were data basic structures which will be used as a reference for the development of lecturer’s performance appraisal data warehouse. Education scheme, Research scheme, and Service scheme were formedfrom data source which collected from systems. Therefore, these schemes can be used to build a warehouse data in the next research. Star Schema is a model has a small number of tables and clear join path, therefore the query can be donequickly. Keywords—data warehouse, star scheme design, lecturer performances